Number Manipulation Strategy: A Model of Experiential Instruction and Interest in Arithmetic Learning of Pupils of Lower Basic Level in Enugu State, Nigeria - Unodiaku, Sochima Stanislus (Journal of Education and Vocational Research, 2021)
The study investigated the efficacy of the number manipulation strategy (NUMAS) as a model of experiential instruction and interest in arithmetic learning for pupils of lower basic levels. The population of the study consisted of 1205 lower basic III level pupils of the 2018/2019 session in Igbo-Etiti Local Government Area (L.G.A.) of Enugu State. A sample of 121 primary five pupils from 4 schools out of 53 primary schools in the study area was randomly sampled. The 121 pupils were composed of 42 males and 79 females used for the study. The study was guided by four research questions and four hypotheses. The hypotheses were tested at a p<.05 level of significance. The instruments used for the study were Arithmetic Test (ART) and Mathematics Interest Inventory Questionnaire (MIIQ) developed by the researcher. The ART and MIIQ instruments were faces validated by experts and their reliability indexes were 0.85 and 0.79 respectively, established using Cronbach alpha and split-half methods respectively. The data obtained with the instruments were analyzed using mean, standard deviations (SD), t-test and analysis of covariance (ANCOVA) statistics. Mean and SD was used in answering the research questions, while t-test and ANCOVA statistics were used in testing the hypotheses at P<.05 level of significance. The findings of the study showed that NUMAS is effective in teaching arithmetic, especially in enhancing the addition and subtraction skills acquisition of the pupils. Gender was found not to be a significant factor of variance in arithmetic achievement when the teaching of arithmetic is NUMAS based. The use of NUMAS was recommended to teachers, lower basic mathematics textbook authors and stakeholders in education, to ensure that NUMAS is adopted and adapted for use in Mathematics classroom instruction and learning.